Antonin Scalia’s Constitutional Textualism: The Problem of Justice to Posterity - Bruce E. Auerbach; Michelle Reinhart (Intergenerational Justice Review)
Antonin Scalia defends his textualist approach to interpreting the Constitution by asserting that the purpose of the Constitution is to restrict the range of options open to future generations by enshrining institutional arrangements and practices in constitutional mandates or prohibitions. For this purpose to be fulﬁlled, justices of the Supreme Court must read the language of the Constitution according to its original meaning. We argue there is little reason to believe that Scalia’s understanding is correct. Neither the language of the Constitution nor the writings of Jeﬀerson or Madison are consistent with Scalia’s interpretation. More importantly, the goal Scalia posits, of seeking to restrict the range of options open to future generations, is intergenerationally unjust.